Pengaruh Celebrity Endorsement Dan Labelisasi Halal Terhadap Keputusan Pembelian Produk Wardah Melalui Brand Image Sebagai Variabel Mediasi (Studi pada Mahasiswa Kampus Swasta Kota Malang) - Laksono, Felicia Averina Laurensia; Mardani, Ronny Malavia; Bastomi, Mohamad (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study was conducted to determine the effect of celebrity endorsement and halal labeling on purchasing decisions through brand image. The method used in this research is quantitative method with explanatory research type. The population of this study were people who had bought Wardah products with a sample size of 65 respondents obtained using non-probability sampling techniques with a purposive sampling approach. This study uses the Structural Equation Modeling (SEM) data analysis method with the help of SmartPLS 4.0 software. The results of this study indicate that celebrity endorsement has no effect on purchasing decisions, halal labeling has no effect on purchasing decisions, celebrity endorsement and halal labeling affect brand image, brand image has no effect on purchasing decisions, celebrity endorsement and halal labeling have no effect on purchasing decisions through brand image. Keywords: Celebrity Endorsement, Halal Labeling, Brand Image And Purchasing Decisions